Cosmopoetics of formless disobedience: leitura contra-colonial do regime da extração no catálogo Lumière - Ribeiro, Marcelo R. S. (2021)
Considering the Lumière catalogue as an inaugural experience of world cinema, this article proposes an anarchival reading of some of its images. Distinguishing the operation of the cinematograph as cosmotechnical device for archiving the world and cosmopoetic apparatus for inventing worlds, I explore the forms of inscription of difference in the Lumière archive, through an archaeology of the sensible. I confront the cinema of attractions with a counter-colonial look, making explicit both the regime of extraction that frames difference and the lines of escape in which a surviving cosmopoetic power emerges, in and between images, through traces of gestures of formless disobedience.